2015
DOI: 10.1002/ajmg.b.32292
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary analysis of microRNA as potential clinical biomarker for schizophrenia

Abstract: MicroRNAs (miRNA, miR) have been implicated as promising blood-based biomarkers for schizophrenia patients. This study aimed to clinically validate miRNA as potential schizophrenia biomarkers. Plasma levels of 10 miRNAs were analyzed using qPCR in a cohort of 61 schizophrenia patients and 62 normal controls, as well as 25 patients particularly selected for a six-week antipsychotic treatment course. Positive And Negative Syndrome Scale (PANSS), Global Assessment Scale (GAS) and Clinical Global Impression (CGI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 37 publications
(50 reference statements)
2
46
0
1
Order By: Relevance
“…Shi et al (2012) suggested that miR-181b, miR-219-2-3p, miR-346, miR-195, miR-1308, miR-92a, miR-17, miR-103 and let-7g are the key players to reflect the SZ illnesses status, 63 while increased expression levels of miR-132, miR-195, miR-30e and miR-7 in plasma, and miR-212, miR-34a and miR-30e in peripheral blood mononuclear cells (PBMCs) was recently reported, this study concluded that miR-30e in plasma is the best potential biomarker. 64 Moreover, PBMCs of SZ patients showed increased expression miR-1273d, miR-1303, miR-21, miR-3064-5p, miR-3131, miR-3687, miR-4428, miR-4725-3p, miR-5096 suggesting that a combination of these miRNAs could serve as potential biomarkers. 65 Up to date, no evidence has been obtained for miR-137 as a diagnostic marker 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2012) suggested that miR-181b, miR-219-2-3p, miR-346, miR-195, miR-1308, miR-92a, miR-17, miR-103 and let-7g are the key players to reflect the SZ illnesses status, 63 while increased expression levels of miR-132, miR-195, miR-30e and miR-7 in plasma, and miR-212, miR-34a and miR-30e in peripheral blood mononuclear cells (PBMCs) was recently reported, this study concluded that miR-30e in plasma is the best potential biomarker. 64 Moreover, PBMCs of SZ patients showed increased expression miR-1273d, miR-1303, miR-21, miR-3064-5p, miR-3131, miR-3687, miR-4428, miR-4725-3p, miR-5096 suggesting that a combination of these miRNAs could serve as potential biomarkers. 65 Up to date, no evidence has been obtained for miR-137 as a diagnostic marker 16 .…”
Section: Discussionmentioning
confidence: 99%
“…While miRNA expression has been examined across a multitude of psychiatric illnesses, encompassing several brain regions, cell types and blood (Bavamian et al, 2015, Fan et al, 2014, Kim, Reimers, 2010, Miller, Zeier, 2012, Moreau, Bruse, 2011, Sun et al, 2015, Walker et al, 2015), to our knowledge this is the first work to examine miRNAs dysregulated as a function of psychiatric illness in AnCg. Additionally, comparing prior work examining miRNA dysregulation in the DLPFC—another brain region of intense interest in the pathology of mental illness—of BP and MDD patients to our results in AnCg, we see little overlap in the specific miRNA species dysregulated as a function of anatomy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“… miR-30e, miR-181b, miR-34a, miR-346 and miR-7 ( of miR-181b, miR-30e miR-132 and miR-432 upon antipsychotic treatment) SCZ (plasma, 62/61) [193] Bavamian et al…”
Section: Refmentioning
confidence: 99%